2013
DOI: 10.4161/sysb.25896
|View full text |Cite
|
Sign up to set email alerts
|

A statistical method to estimate DNA copy number from Illumina high-density methylation arrays

Abstract: A statistical method to estimate DNA copy number from Illumina high-density methylation arrays, Systems Biomedicine, 1:2, 94-98,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Herein, we propose a strategy for the statistical analysis of CNVs with data from methylation arrays using bioinformatics tools (conumee and ChAMP) ( 15 ). Previous publications have shown that they provide analogous results to the gold-standard technique for CNV analysis (CGH arrays) ( 26 , 27 ). Nevertheless, these tools focus on CNV representation ( 15 , 26 , 28 ) and are not designed for the statistical analysis of differences between different groups.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Herein, we propose a strategy for the statistical analysis of CNVs with data from methylation arrays using bioinformatics tools (conumee and ChAMP) ( 15 ). Previous publications have shown that they provide analogous results to the gold-standard technique for CNV analysis (CGH arrays) ( 26 , 27 ). Nevertheless, these tools focus on CNV representation ( 15 , 26 , 28 ) and are not designed for the statistical analysis of differences between different groups.…”
Section: Discussionmentioning
confidence: 83%
“…Susceptibility to psoriasis or disease severity has been associated with CNVs in certain genes such as CCL4/CCL4L ( 6 ), LCE3B and LCE3C ( 7 ) and DEFB ( 8 ). However, we have not found CNVs associated with anti-TNF drug response or with the appearance of psoriasiform reactions in the regions containing these genes.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy allows for maximizing the information gathered with such an expensive technique as methylation microarrays. In addition, CNV determination from methylation arrays provides similar results to the gold-standard technique for CNV analysis (CGH arrays) [37,38]. Nevertheless, quantifying CNV differences between two groups is still very challenging since most of these tools are focused on CNV representation [37,39,40].…”
Section: Discussionmentioning
confidence: 99%